Validity of self-reported anthropometry in adult Mexican women - Eduardo Ortiz-Panozo (Salud Pública de México, 2017)
Objective. To compare direct and self-reported anthropometry in Mexican women. Materials and methods. Women aged 30-72 years, participating in the Mexican Teachers’ Cohort, completed a questionnaire with their anthropometric data in 2006-2008. After eleven months (median time), technicians performed anthropometry in 3 756 participants. We calculated correlations and multivariable-adjusted mean differences between direct and self-reported anthropometric measures. Results. Correlations between direct and self-reported anthropometric measures ranged from 0.78 (waist circumference) to 0.93 (weight). On average, women over-reported their height by 2.2 cm and underreported their weight, body mass index (BMI) and waist and hip circumferences by 1.3 kg, 1.3 kg/m2, 1.8 cm and 1.9 cm, respectively. Errors in self-reported anthropometry increased with rising measured BMI and were also independently associated with age, education and socioeconomic status. Conclusion. Self-reported anthropometry is sufficiently valid for epidemiological purposes in adult Mexican women. Errors in selfreported anthropometry might result in underestimation of the prevalence of overweight and obesity.